Production and Thermal Exchange of Conditional Peptide‐MHC I Multimers. (26th July 2019) - Luimstra, Jolien J.; Franken, Kees L. M. C.; Garstka, Malgorzata A.; Drijfhout, Jan W.; Neefjes, Jacques; Ovaa, Huib
Abstract: Cytotoxic CD8 + T cells mediate cellular immunity through recognition of specific antigens presented by MHC class I on all nucleated cells. Studying T cell interactions and responses provides invaluable information on infection, autoimmunity and cancer. Fluorescently labeled multimers of MHC I can be used to quantify, characterize, and isolate specific CD8 + T cells by flow cytometry. Here we describe the production and use of conditional MHC I multimers that can be loaded with peptides of choice by incubating them at a defined temperature. Multimers are folded with a template peptide that forms a stable complex at low temperature, but dissociates at a defined elevated temperature. Using this technology multiple MHC I multimers can be generated in parallel, to allow staining and isolation of large sets of antigen‐specific CD8 + T cells, especially when combined with barcoding technologies. © 2019 The Authors.